Modelling and Estimating Modal Share in European Transport - Giovanni Russo; Aura Reggiani; Peter Nijkamp (Tinbergen Institute, 2001)
International and interregional trade and transport are on the rise and hence, there is a clear needfor reliable estimates of transport flows. However, the available databases and estimation methodsare not yet satisfactory for analytical and predictive purposes.In this paper we explore the use of different statistical techniques in order to examine the spatialflow pattern of freight transport among competing transport modes.Freight transport has specific peculiarities that are different from passenger transport. We arguethat a logit model, the most commonly used technique in the empirical analysis of passengerflows, is not always appropriate for the analysis of freight flows, unless the interdependencebetween the decision making regarding the shipment of individual units of freight belonging tothe same shipment is correctly modelled.In the paper, we will focus on the analysis of aggregate freight transport flows of the type thatmay be generated from conventional spatial interaction models. In particular, adjusted estimationtechniques alternative to the logit model will be employed to analyze the transport flows of twoproducts, chemical products and foodstuffs, based on an European interregional data set.We will conclude the paper by discussing various caveats encountered during the empiricalanalysis.
Keywords: 330; Chemikalie; Nahrungsmittel; Verkehrsaufkommen; Güterverkehr; Verkehrsökonomik; Theorie